Marguerite Yourcenar and the Phallacy of Indifference - Linda Klieger Stillman (Studies in 20th & 21st Century Literature, 1985)
At first glance, the works of Marguerite Yourcenar seem far removed from any specifically female or feminist preoccupation and the author herself vigorously affirms the universality of her writing. Nevertheless, an intertextual reading of her fiction, autobiography, and interviews reveals that sexual difference is in fact an important aspect ofher texts. An analysis of repetitive lexical and rhetorical patterns clearly articulates Yourcenar's repressed feminine discourse.
Keywords: Marguerite Yourcenar; female; feminist; feminism; intertextual reading; intertextuality; sexuality; gendered; lexical pattern; rhetorical pattern; feminine discourse